The Use of Fibrin-based Tissue Adhesives for Breast in Reconstructive and Plastic Surgery - Chen, Kuo; Sinelnikov, Mikhail Y.; Nikolenko, Vladimir N.; Reshetov, Igor V.; Cao, Yu; Li, Zhi; Kochurova, Ekaterina V.; Nikolenko, Svetlana N.; Avila-Rodríguez, Marco; Somasundaram, Siva G.; Kirkland, Cecil E.; Aliev, Gjumrakch (Current Topics in Medicinal Chemistry, 2019)
Background: Breast plastic surgery is a rapidly evolving field of medicine. The modern view of surgical trends reflects the desire to minimize complications and introduce advanced technologies. These always will be priorities for surgeons. Reconstructive surgery, a branch of plastic surgery focusing on restoration of lost functional and aesthetic component, seeks to enhance psychological rehabilitation and improves the quality of life, as well as aesthetic recovery. Objective: This review addresses the action of fibrin agents and their effect on the quality of surgical hemostasis. Discussion and Conclusion: The fundamental goals for the surgeon are to perform a minimally traumatic intervention and to prevent any form of complication. Achieving complete hemostasis is an intraoperative necessity. Timely prevention of bleeding and hemorrhagic phenomena can affect not only the outcome of the operation, but also the incidence of postoperative complications. Topics include the integrity of microvascular anastomoses, tissue adhesion, and the incidence of seromas and hematomas associated with fibrin glue usage. The literature on fibrin adhesives with respect to prevention of postoperative complications, and the effectiveness with active drainage also are analyzed.
Keywords: Aesthetics